Pengaruh Beban Kerja Dan Stres Kerja Terhadap Produktivitas Karyawan Hotel Sangga Buana - Alam, Fajar Nur; Apriadi, Deri (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses how workload and work stress can affect employee productivity levels at Hotel Sangga Buana. The busy hotel industry requires employees to continue working optimally amidst high pressure. This study uses a quantitative approach with observation and survey methods by distributing questionnaires to 48 respondents. Data were analyzed using multiple linear regression. The results show that workload has a negative but insignificant effect on productivity, while work stress has a positive and significant effect. The percentage of influence of both variables on productivity is 12.8%. This finding indicates the need for proper management of workload and work stress so that employees remain productive.